Study on the Clinical Features of Parkinson's Disease With Probable Rapid Eye Movement Sleep Behavior Disorder - Long, Kexin; Wan, Changmin; Xiang, Yaqin; Liu, Jiabin; Xu, Qian; Sun, Qiying; Wang, Zhiqin; Tian, Yun; Fang, Liangjuan; Yang, Yang; Yan, Xinxiang; Tang, Beisha; et al. (Frontiers in Neurology, 2020)
To investigate the clinical features and associated factors of Parkinson's disease (PD) patients with probable rapid eye movement sleep behavior disorder (PD-pRBD).A total of 2440 patients with clinically established or clinically probable PD were divided into two groups: PD-pRBD and PD without pRBD group (PD-NRBD) according to the RBD questionnaire-Hong Kong (RBDQ-HK). Data collection included demographic data, basic clinical history and the assessment of motor and non-motor symptoms. Based on the onset time of pRBD and the motor symptoms in PD, PD-pRBD patients were further divided into pRBD prior to PD (PD-prRBD) group and pRBD posterior to PD (PD-poRBD) group. Clinical features were compared between PD-pRBD group and PD-NRBD group, as well as PD-prRBD group and PD-poRBD group. And the associated factors of pRBD were also explored. The prevalence of pRBD was 41.4% in our PD cohort. Compared with the PD-NRBD group, the PD-pRBD group had longer disease duration and more severe motor symptoms especially rigidity, bradykinesia, posture gait, frozen gait. And the PD-pRBD group had significantly higher levodopa equivalent dose daily (LEDD) and higher ratio of dyskinesia, wearing-off and late stage of H-Y stage. The score of non-motor symptom rating scale (NMSS), cognitive impairment, Parkinson disease sleep scale (PDSS), excessive daytime sleepiness (EDS),constipation, hyposmia, depression and the 39-item Parkinson's disease questionnaire (PDQ-39 ) also appeared worse in the PD-pRBD group. Significant differences widely existed between PD-prRBD group and PD-poRBD group, including educational level, motor subtype, disease duration, disease’s progression, UPDRS-II, UPDRS-III, tremor, rigidity, bradykinesia, posture gait, frozen gait, LEDD, dyskinesia, wearing-off, H-Y stage, NMSS-6 , PDSS and social support. Late-onset PD (LOPD), long course of disease, high UPDRS-I score, high NMSS-4 score, low PDSS score, constipation and hyposmia were all identified as the risk factors for PD-pRBD. Comparing with PD-NRBD group, PD-pRBD group may have more severe motor symptoms, motor complications and non-motor symptoms, as well as poorer quality of life; LOPD, long disease duration, high UPDRS-I score, high NMSS-4 score, low PDSS score, constipation and hyposmia can be risk factors for RBD in PD; Differences also occur between PD-prRBD group and PD-poRBD group.